2001
DOI: 10.1063/1.1333737
|View full text |Cite
|
Sign up to set email alerts
|

Thermal lens scanning of the glass transition in polymers

Abstract: In this article we discuss the use of the thermal lens technique for investigating the thermal properties of polymers as a function of temperature. It is also discussed how the experimentally determined thermal lens parameters can be used to locate the glass transition in polymers. The methodology is tested using a solution casted films of poly͑vinyl chloride͒ as a testing sample. A comparison with conventional differential scanning calorimetry data is made. It is proposed that the current transient thermal le… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
9
0

Year Published

2002
2002
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(11 citation statements)
references
References 37 publications
2
9
0
Order By: Relevance
“…On the other hand, for the temperatures above 70 K the temperature dependence of D is determined by variation of both the mean free path and the sound velocity. This dependence happens due to the fact that at temperatures >70 K the mean free path in amorphous materials coincides, in a first approximation [11,18], with the mean distance between two neighboring atoms, whereas the sound velocity is proportional to (k e / m) 1/2 , in which k e is the characteristic elastic constant of the bonding forces between two neighboring atoms with effective mass m. In other words, our results show that in the temperature interval 20 < T < 70 K the thermal diffusivity temperature dependence is dominated by the 1/T variation of the mean free path, while at high temperatures, the change of the sound velocity also contributes to the small variation of the thermal diffusivity.…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…On the other hand, for the temperatures above 70 K the temperature dependence of D is determined by variation of both the mean free path and the sound velocity. This dependence happens due to the fact that at temperatures >70 K the mean free path in amorphous materials coincides, in a first approximation [11,18], with the mean distance between two neighboring atoms, whereas the sound velocity is proportional to (k e / m) 1/2 , in which k e is the characteristic elastic constant of the bonding forces between two neighboring atoms with effective mass m. In other words, our results show that in the temperature interval 20 < T < 70 K the thermal diffusivity temperature dependence is dominated by the 1/T variation of the mean free path, while at high temperatures, the change of the sound velocity also contributes to the small variation of the thermal diffusivity.…”
Section: Discussionmentioning
confidence: 95%
“…When operated in the transient mode, the method reduces the heat transfer as compared to steady state techniques. Indeed, it has been used recently to obtain optical and thermal properties during phase modification of a wide range of materials [5,[10][11][12]. In those studies, the thermo-optical properties of the samples were investigated as a function of temperature in a range of temperatures from 300 to 580 K. More recently, and of interest for this work, the technique was applied to determine D, K and ds/dT of glass samples from 20 to 300 K [6].…”
Section: Introductionmentioning
confidence: 99%
“…3. It can be seen that the T g of PVC/P-NAs were significantly lower than that of unplasticized PVC film [13,25,26], which indicated that P-NAs significantly improved the plasticization efficiency of PVC film because of the increase of free volume of the PVC films with the addition of P-NAs plasticizers then increasing the plasticization performance [27]. It is important to note that the T g value of PVC/P-MPO-NA (218.408C) was lower than that of PVC/P-BDO-NA and PVC/P-DEG-NA (216.288C and 214.578C, respectively).…”
Section: Differential Scanning Calorimetrymentioning
confidence: 99%
“…This comprises the determination of low optical absorption coefficients, 20,21 Soret effect, 22 investigation of photobleaching processes, characterization of mass and thermal diffusion properties of fuels and biofuels, [23][24][25][26] dyes, [27][28][29] micellar solutions, 30 and photosensitizers. [31][32][33][34] The method can also be used to study thermal and optical properties of polymers and glasses, [35][36][37][38][39][40] in addition to the pharmacological and biological applications and determination of heavy metals. [41][42][43][44][45] There have been several reviews on TL applications in the literature.…”
Section: Introductionmentioning
confidence: 99%